Development of a futsal sports curriculum model aged 6-8 years at the Super Junior club in Malang City - Novenda, Dwi; Widiawati, Prisca (Universitas Negeri Malang, 2025)
Background: The lack of a structured futsal curriculum for children aged 6-8 years in futsal clubs, especially in Super Junior Club Malang, causes limitations in developing techniques, skills, and long-term athlete development. Objective: This is for developing a futsal curriculum model at the Super Junior Club of Malang City, which is presented as a curriculum for learning. Methods: The research and development model used in the study is to develop a curriculum model. Development research This uses the ADDIE method with steps study as follows: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. This is done using a questionnaire and sheet valuation. Results of interviews that have been done do Not yet exist. Possible guidelines​ and curricula can be used to create training programs. Excess from study This includes: 1) becoming guidelines beginning in making training programs, 2) making things easier for trainers to determine goals in the training program. The weaknesses of the study include: 1) limitations in election group age certain, 2) not too many training models, and 3) the curriculum must keep updating along with the development of futsal sport. Result: Based on the results, an analysis by the validator is obtained. The average percentage was 88.07% from material validators, 97% from media validators, and 94.7% from group tests conducted on Malang City Super Junior Club students. Conclusion: Curriculum Model Development Sport Futsal Age 6-8 Years at the Malang City Super Junior Club is considered worthy of use. Future research could explore the effectiveness of implementing this futsal curriculum in improving players' technical and tactical skills and examine its impact on the long-term development of early athletes in various clubs and regions.